International students’ perceptions of classroom Malaysian English variety - Li, Teh June; Pilus, Zahariah (2015)
Numerous studies comparing native and non-native English teachers (Coskun, 2013; Diaz, 2015; Madrid & Canado, 2004; Walkinshaw & Duong, 2012) have found that ESL students prefer native teachers for teaching speaking skills and pronunciation. In other words, non-native teachers are viewed as less superior in matters related to spoken language. This study explores the issue by examining the perceptions of international students of the English variety used by their Malaysian teachers in the English language classes. 30 international students at the Centre of Languages, Pre-University Academic Development (CELPAD) from various countries such as Algeria, China, and Sudan participated in the study. They were given a writing task which required them to state their views on the teachers’ spoken English in terms of understanding, speech rate, pronunciation, vocabulary usage, sentence usage and nativeness. Findings from this study will reveal how Malaysian English is perceived by other non-native speakers as well as their acceptance of Malaysian English as a non-native variety.